Courting the community: organizational flexibility and community courts - Zozula, Christine (Criminology & criminal justice, 2018)
This article examines how a community court in the United States framed its mission to a diverse population of stakeholders. Drawing from 11 months of ethnographic data, I show how community courts’ embrace of both punitive and therapeutic goals help the courts appeal to a variety of audiences. I argue that by adopting a flexible mission which allows for both punishment and treatment, community courts are better able to create and maintain organizational legitimacy. This article not only adds to the literature on the flexibility of punishment logics, but it also brings a new focus by considering the organizational utility of mutable penal goals.